Performa Fungi Mikoriza Arbuskula dan Pueraria phaseoloides yang Dipupuk Tepung Tulang dengan Ukuran dan Dosis Berbeda - A D Nusantara; C Kusmana; I Mansur; L K Darusman; . Soedarmadi (Faculty of Animal Science, Bogor Agricultural University, 2011)
Bone meal is a natural source of calcium and phosphorus required for plant growth, but phosphorus can cause problems if they occur in high concentrations particularly will inhibit growth of mycorrhizal fungi. The aim of this study was to find the best diameter size and dosage of bone meal for increasing growth of forage legume Pueraria phaseoloides and for producing arbuscular mycorrhizal fungi (AMF) Glomus etunicatum inoculant. A glass house experiment was laid out in a randomized block design consisted of 13 treatments (control and 12 combination of different diameter size and weight of bone meal) and replicated three times. Bone meal and artificial fertilizer resulted the same effect (P>0.05) on dry matter of P. phaseoloides. Application of 25–40 mg with <250 µm diameter significantly (P<0.05) increased dry matter production. Bone meal reduced significantly (P<0.05) root colonization but increased significantly number of spores compared to that of artificial fertilizer. Reducing bone meal diameter significantly increased root colonization and number of spores of AMF G. etunicatum.